2022
DOI: 10.21203/rs.3.rs-1546115/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role and Mechanism of Cotrimoxazole Resistance to Talaromyces marneffei fungus in vitro

Abstract: Background Talaromyces marneffei (formerly Penicillium marneffei) is an important thermally dimorphic fungus endemic which is characterized by one of the most frequent opportunistic infections in HIV/AIDS patients, mainly prevalent in Southeast Asia, southern China, and northeastern India. Cotrimoxazole(CTX) inhibits folic acid synthesis which is important for the survival of many bacteria, protozoa, and fungi, thereby commonly used to prevent several opportunistic infections among HIV/AIDS patients. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This has now become an option, as one retrospective study by Jiang et al [ 89 ] observed that patients on co-trimoxazole prophylaxis (a total of 3359 persons receiving ART from 2005 to 2016) had a significantly lower T. marneffei infection rate than those not on co-trimoxazole (4.11% versus 7.53%, respectively). Furthermore, co-trimoxazole was observed to inhibit T. marneffei growth in an ex vivo THP1 macrophage model [ 90 ]. The reported mechanism indicated that co-trimoxazole blocks dihydropteroic acid synthase (DHPS), dihydrofolate synthase (DHFS), and dihydrofolate reductase (DHFR), which are all utilized by T. marneffei to promote growth.…”
Section: Treatmentmentioning
confidence: 99%
“…This has now become an option, as one retrospective study by Jiang et al [ 89 ] observed that patients on co-trimoxazole prophylaxis (a total of 3359 persons receiving ART from 2005 to 2016) had a significantly lower T. marneffei infection rate than those not on co-trimoxazole (4.11% versus 7.53%, respectively). Furthermore, co-trimoxazole was observed to inhibit T. marneffei growth in an ex vivo THP1 macrophage model [ 90 ]. The reported mechanism indicated that co-trimoxazole blocks dihydropteroic acid synthase (DHPS), dihydrofolate synthase (DHFS), and dihydrofolate reductase (DHFR), which are all utilized by T. marneffei to promote growth.…”
Section: Treatmentmentioning
confidence: 99%
“…we take the user through the routes of creating a new user or login using automata theory concepts. [6] The growing use of internet-based banking and shopping has seen the growth of various e-commerce payment systems and technology has been developed to increase, improve and provide secure e-payment transactions. [7] The role of slogans becomes crucial as competition among online marketplaces have also been tougher, thus demands the need for catchy, impressive slogans.…”
Section: Literature Surveymentioning
confidence: 99%